The gliadin-CFTR connection: new perspectives for the treatment of celiac disease - Luigi Maiuri; Valeria R. Villella; Valeria Raia; Guido Kroemer (BMC, 2019)
Abstract Familial loss-of-function mutations of the gene coding for the cystic fibrosis transmembrane conductance regulator (CFTR) channel protein cause cystic fibrosis (CF), the most frequent inherited life-threatening disease in the Caucasian population. A recent study indicates that the gluten/gliadin-derived peptide (P31-43) can cause CFTR inhibition in intestinal epithelial cells, thus causing a local stress response that contributes to the immunopathology of celiac disease (CD). Accordingly, an increased prevalence of CD has been observed in several cohorts of CF patients. CD is characterized by a permanent intolerance to gluten/gliadin proteins occurring in a proportion of susceptible individuals who bear the human leukocyte antigen (HLA) DQ2/DQ8. In CD, perturbations of the intestinal environment, together with the activation of the innate immune system by P31-43, are essential for rendering other immunodominant gliadin peptide fully antigenic, thus triggering an adaptive immune response with an autoimmune component. P31-43-induced CFTR inhibition elicits the danger signals that ignite the epithelial stress response and perturb epithelial proteostasis. Importantly, potentiators of CFTR channel gating, such as the FDA-approved drug Ivacaftor, prevent P31-43 driven CFTR inhibition and suppress the gliadin-induced stress response in cells from celiac patients, as well as the immunopathology developing in gliadin-sensitive mice. Thus, CFTR potentiators may represent a novel therapeutic option for celiac patients.